Medios y métodos de entrenamiento de los especialistas en velocidad y pruebas combinadas de la Región de Murcia - Alcaraz Ramón, Pedro; Palao Andrés, José Manuel (KRONOS, 2007)
Available infrastructure and materials and planning methods used by coaches affect athletes’ training. The aim of this paper was to study Murcia area (Spain) sprinter and multi-event athletes training conditions. Studied athletes body was composed of 15 sprinter and 15 multi-events athletes (21 males and 9 females, 19-20 years old and seven years of systematic training average). Athletes filled out a survey aboyt available and used infrastructure and materials, and training methods, types, frequency and characteristics. A descriptive analysis was done with the variables studied (average and percentages). Results show that majority of the athletes train in tartar surface track & field court with material recommended by different authors to develop sprinters and general and specific strenght available. Athletes studied train between 4-5 times a week in 2-3 hours group or specific sessions.